Quadricuspid Aortic Valve Repair Facilitated by Geometric Ring Annuloplasty. Issue 4 (July 2021) - McGuire, Joseph A.; Hayanga, Heather K.; Hayanga, Jeremiah W.; Sloyer, Daniel; Ellison, Matthew; Wei, Lawrence; Rankin, J. Scott; Badhwar, Vinay
Quadricuspid aortic valve (QAV) is a rare congenital anomaly often associated with aortic insufficiency. The exact anatomy of QAV is variable, and most cases have undergone aortic valve replacement. With the recognition that aortic valve repair achieves superior patient outcomes as compared to replacement, a systematic approach to autologous reconstruction of QAV is needed. This article reports 2 cases having successful repair utilizing geometric aortic annuloplasty rings, and describes a proposed scheme for repairing most QAV defects, based on relative leaflet and commissural characteristics. Using either tri-leaflet or bicuspid ring annuloplasty, the normal sub-commissural triangles can be remodeled into a 120° or 180° configuration, respectively, and then the leaflets can be sutured and plicated to fit annular geometry. With this approach, most quadricuspid valves potentially could undergo autologous reconstruction.